Prophylactic ankle supports effects on time to stabilization, perceived stability and ground reaction force during lateral landing in female collegiate athletes with chronic ankle instability - Ali Yalfani; Zahra Raeisi (BMC, 2021)
Abstract Background This study was designed to investigate effects of Kinesiotape (KT) with closed basket weave method and lace-up braces (LB) on the vertical time to stabilization, peak vertical ground reaction force (PvGRF), and time to PvGRF as well as perceived stability during lateral landing of participants with chronic ankle instability before and after fatigue. Methods Thirty female college athletes with chronic ankle instability of three conditions (control, KT, and LB) performed lateral landing from a 30 cm high step on the plantar pressure platform pre and post fatigue. Results The pre-test findings on the rearfoot, of LB indicated negatively increased the PvGRF force (F2,58=3.63, P = 0.04) and decreased the time to PvGRF (F2,58=4.67, P = 0.01). The Bonferroni post-hoc testing revealed LB condition increased the PvGRF than the control (P = 0.002) and KT (P = 0.038). Also, the post-hoc testing showed LB condition decreased the time to PvGRF force than the control (P = 0.05) and KT (P = 0.01). The LB negatively prolonged vertical time to stabilization in the forefoot (F2,58=6.74, P = 0.002) and rearfoot (F2,58=6.13, P = 0.004) after fatigue. The post-hoc testing revealed LB condition generated a slower vertical time to stabilization than the control and KT conditions (P ≤ 0.05). The use of KT had no positive effects as elevated the PvGRF in the forefoot post fatigue (F2,58=7.11, P = 0.002). The post-hoc test uncovered that KT augmented the PvGRF than control (P = 0.01) and LB (P < 0.001). On the other hand, using KT had psychological effects at pre-fatigue which resulting significantly greater in perceived stability compared to other conditions (F2,58=9.65, P < 0.001). The post-hoc test showed that using KT increased perceived stability than LB (P = 0.004) and control (P < 0.001). Moreover, perceived stability improved significantly in KT and LB compared to the control condition at the post-fatigue (P ≤ 0.001). Conclusions Despite the positive psychological impact of the prophylactic ankle supports, there were no positive effect on the vertical time to stabilization, PvGRF, and time to PvGRF. Further studies are needed to distinguish the psychological and actual effects of prophylactic ankle supports on athletes with chronic ankle instability.